Shohimardonsoy daryo havza landshaftidagi meliorativ holat, geoekologik vaziyat va ularni yaxshilash masalalari (SCIENCE and SOCIETY, 2024)
The article are considered in the context of Global climate change, reclamation changes in the landscape of the Shohimardonsoy River Basin and the geoecological situation. Currently, for the development of the» nature-man-farm " system, the issues of improving these conditions are reflected in the river basin landscape. A complex approach is of particular importance when conducting research on the landscape condition of the shahimardon River Basin, the reason is that these studies have a natural and social essence at the same time.